(3GdLGeY GdUZjQs - (3TeS GdOjf CHh YHO Gddg eMeO GdcdGFjs ((3eUQ GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdbOjQ hHYO agPG cJGH LeYJg ai CUhd GdYQHjI hSejJg GdLGeY GdUZjQ hgh jTJed Ydi ebOeI hYTQI CHhGH hNGJeI CeG GdebOeI aajgG eSGFd GdHGH GdChd ai GdGSe GdKGfi ai GdaYd GdKGdK ai GdMQa s
(3BNQgG (B:s
(3hGYde habc Gddg Edi GdNjQGJ Cf LejY eG ai gP GdcJGH ef UhGH hJMbjb agh ef cdGe GdYdeGA heG hbY ajg ef ZdW hJNdjW hSgh aef ShA agei hUdi Gddg Ydi eMeO hBdg hUMHg hSde JSdjekG cKjQkG OGFekG CHOkG hQVi Gddg Yf GdUMGHI hGdBd CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg eWGdH ddcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs